Penerapan Terapi Minum Teh Hijau Dalam Mengontrol Tekanan Darah Pada Penderita Hipertensi Pada Keluarga Ibu A di Kelurahan Bambu Apus RT 14 RW 03 Kecamatan Cipayung Jakarta Timur - Ratika, Sisilia Febriana; Samsuni, Samsuni (Universitas Respati Indonesia, 2024)
Hypertension is a condition in which blood pressure rises chronically (long term) and has the potential to cause extreme illness or death to the individual. Individuals who are diagnosed as suffering from hypertension if there is an indication that the systolic blood pressure is greater than 140 mmHg and the diastolic blood pressure is less than 90, which is more, if treatment is not carried out intensively and treatment can also be carried out early, can have a high risk of causing degenerative disease, namely retinopathy. , thickening of the heart wall, kidney damage, coronary heart disease, rupture of blood vessels, stroke, can also result in sudden death. The family has an important role in efforts to improve health and reduce the risk of disease in society because the family is the smallest unit in society, the role of the family is very important in every aspect of family health care, for this reason the family plays a role in determining the type of care needed by the family. Family nurses have a role, namely helping families to solve health problems by increasing the family's ability to carry out health care functions and tasks. Based on data, one effort to lower blood pressure is by giving green tea (Camelia sinensis). Tea has the main properties that come from the polyphenols contained in it.